South Africa's peacemaking strategy in southern Africa: The case of Lesotho 1998-2002 - Mmutle, Simon (My University, 2008)
Post apartheid South Africa emerged at a time when the region was experiencing violent conflicts that had the potential of spreading to other countries in the region. South Africa, which was partly isolated during the apartheid era, woke up to the reality of the fact that it was part of the Southern African region and could not remain impartial to the political instabilities experienced by its neighbours. Since the region played a crucial part in the negotiated settlement of the dispute in South Africa in a peaceful manner, it was therefore in its interests to solve the political instabilities in the region peacefully. Tools of conflict resolution, especially peacemaking which encourages warring faction to negotiate, became the strategy South Africa used to solve the regional instabilities. The purpose of this thesis is to evaluate the peacemaking efforts by South Africa in the Southern African region by examining instability in Lesotho as a case study. The aim of the thesis is to test the hypothesis that the South African peacemaking strategy in Southern Africa yielded positive results. In investigating South Africa’s peacemaking strategy, using Lesotho as a case study, the thesis examines the causes of the political instability in the country and how South Africa tried to solve it. The three main political parties in Lesotho, i.e. the Basotho National Party, the Lesotho Congress Party and the Marema Tlou Party, were the main parties that contested the elections in Lesotho. Thus they were the parties that were involved in the negotiating process spearheaded by South Africa. South Africa, Botswana and Zimbabwe formed the South African Development Community Troika (SADC) Troika that played an important role in bringing about limited stability in Lesotho; the aim being to address the main causes of instability in the country.